Penerapan Asas Kebebasan Berkontrak dalam Kontrak Baku Pemerintah Berdasarkan Studi Kasus Perjanjian Sewa Rusunawa Rawa Bebek - Erna Wulansari (Program Studi Ilmu Hukum, Universitas Kuningan, 2026)
Legal relationships in modern society cannot be separated from agreements as legal instruments that establish the rights and obligations of the parties. One of the fundamental principles of contract law is the principle of freedom of contract, which grants parties the autonomy to determine the contents and form of an agreement. However, in practice, the application of this principle in government standard contracts often encounters issues of unequal bargaining power, potentially limiting the parties' freedom to give genuine consent. This study aims to analyze the regulation of the principle of freedom of contract under Indonesian civil law and its application in government standard contracts through a case study of the Rusunawa Rawa Bebek lease agreement. This research employs a normative juridical method using statutory and conceptual approaches supported by library research. The findings indicate that, normatively, the principle of freedom of contract is recognized under Article 1338 of the Indonesian Civil Code. Nevertheless, its application in the Rusunawa Rawa Bebek lease agreement does not fully reflect the parties' free will, as the contract was unilaterally drafted by the government and signed under conditions of hardship following forced eviction. This situation resulted in an imbalance of bargaining positions and indicated the presence of defective consent, which may affect the validity of the agreement. Therefore, the application of the principle of freedom of contract in government standard contracts should be accompanied by adequate protection for weaker parties and the implementation of the principles of justice and contractual balance.